Evaluation of Mechanical Properties of Kevlar Fibre Reinforced Aluminium 6061 Sandwich Composites - Senthil Kumar, B; Muruganandam, D; Jayapriya, J (International Journal of Engineering and Technology, 2018)
In the present scenario composite materials has got a good value in making a high strength component. Kevlar fibre reinforced composite have a good property of making materials with high strength and low weight. With proper fabrication these Kevlar fibres will produce good property in making components that will be used for specific applications. Our project is dealt with the preparation of a laminate using Kevlar fibre reinforced composite in 0o-90o orientation by using epoxy resin as adhesive and to analyze the mechanical properties of that particular laminate and study that it has high mechanical properties or not. Main objective of this project is to make a composite laminate with high strength, high stiffness, and low weight for various applications.Â